Meliponini neotropicais: o gênero camargoia moure, 1989 (apinae, apidae, hymenoptera) - Camargo, João M. F. de (Arquivos de Zoologia, 1996)
Camargoia nordestina, sp. n., is described from the dry valleys of Piaui state, NE Brazil. It differs from C. camargoi by the yellow maculations ofparaocular areas ending at the level of superior tangent of antennal sockets, basitarsi II and tibiae and basitarsi III blackish, microtrichiae of anterior wing uniformly fuscous and the median ocellus above the orbital tangent. C. camargoi has the yellow paraocular maculation reaching the middle of the front; the basitarsi and tibiae are yellowish, only slightly darkish on apex; the microtrichiae fuscous at the anterior wing apex and yellowish at basis, median ocellus reaching the level of orbital tangent. From C. pilicornis, it differs by the very shorter setae of the antennal scape with about 1/4 of its diameter. C. pilicornis has the setae longer or as long as the diameter of scape. The subterraneous nest of, C. nordestina is described in detail. Some considerations about possible convergency of architectonic attributes . among the nests of Camargoia, Geotrigona and Schwarziana are presented. The result of a cladistic analysis suggests Camargoia as sister-group of Ptilotrigona.